Comparative analysis of replication and immune evasion among SARS-CoV-2 subvariants BA.2.86, JN.1, KP.2, and KP.3 - Yanping Hu; Jing Zou; Michael D. Nguyen; Hope C. Chang; Jason Yeung; Haiping Hao; Pei-Yong Shi; Ping Ren; Xuping Xie (mBio)
ABSTRACT The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) BA.2.86 sublineage and its descendants (JN.1, KP.2, and KP.3) have acquired key recurrent mutations (R346T, L455S, F456L, and Q493E) and became predominant strains, following the epidemiological progression: BA.2.86→JN.1→KP.2→KP.3. However, the mechanisms driving this succession remain incompletely understood. In this study, we assessed the replication fitness of SARS-CoV-2 strains containing spike sequences from BA.2.86 and its descendants (JN.1, KP.2, and KP.3) in primary human airway epithelium cells and their sensitivity to neutralization by human sera. Our analysis revealed reduced spike cleavage in JN.1 and KP.2 virions compared to BA.2.86 and KP.3, indicating that receptor-binding domain (RBD) mutations L455S and Q493E, despite being distant from the furin cleavage site, can influence spike cleavage. JN.1, with the additional L455S mutation, replicated more slowly than BA.2.86 but was more resistant to neutralization by XBB.1.5-infection sera, suggesting that immune evasion driven by the L455S mutation is the primary factor behind the BA.2.86-to-JN.1 transition. KP.2, carrying additional R346T, L455S, and F456L mutations, showed both enhanced replication and increased resistance to neutralization by JN.1-infection sera, indicating that the combined effects of these mutations on immune evasion and viral fitness drive the JN.1-to-KP.2 shift. The latest strain, KP.3, derived from JN.1 with the L455S, F456L, and Q493E mutations, demonstrated even greater replication than KP.2 while maintaining similar neutralization sensitivity to JN.1-infection sera, suggesting that Q493E further enhances viral replication and drives the KP.2-to-KP.3 transition. These findings highlight how specific recurrent spike mutations in BA.2.86 descendants fine-tune viral replication fitness and immune evasion, promoting their emergence and dominance.IMPORTANCEThe study advances our understanding of the roles of immune evasion and replication fitness in driving the evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from the BA.2.86 sublineage to its descendants (JN.1, KP.2, and KP.3). Through head-to-head comparisons of the replication fitness of recombinant SARS-CoV-2 strains containing spike sequences from BA.2.86 and its descendants in primary human airway epithelium cells, alongside assessments of their neutralization sensitivity to human sera, we revealed how recurrent mutations R346T, L455S, F456L, and Q493E in the receptor-binding domain (RBD) fine-tune immune evasion and viral replication fitness, underscoring the critical need for updated countermeasures to combat newly emerged SARS-CoV-2 variants. Additionally, our analysis showed that the L455S and Q493E mutations in the RBD can influence spike cleavage, offering new insights into SARS-CoV-2 spike biology.